High quality draft genome sequence and description of Occidentia massiliensis gen. nov., sp. nov., a new member of the family Rickettsiaceae - Mediannikov, Oleg (Stand Genomic Sci, 2014)
The family Rickettsiaceae currently includes two genera: Orientia that contains one species, Orientiatsutsugamushi, and Rickettsia that contains 28 species. Occidentia massiliensis gen. nov., sp. nov. strain OS118(T) is the type strain of O. massiliensis gen. nov., sp. nov., the type species of the new genus Occidentia gen. nov. within the family Rickettsiaceae. This strain, whose genome is described here, was isolated in France from the soft tick Ornithodoros sonrai collected in Senegal. O. massiliensis is an aerobic, rod-shaped, Gram-negative, obligate intracellular bacillus that may be cultivated in BME/CTVM2 cells. Here we describe the features of O. massiliensis, together with the complete genomic sequencing and annotation. The 1,469,252 bp long genome (1 chromosome but no plasmid) contains 1,670 protein-coding and 41 RNA genes, including one rRNA operon.